Effectiveness of a parent‐targeted video on neonatal pain management: Nonrandomized pragmatic trial - Ligyana Korki de Candido; Denise Harrison; Maria de La Ó Ramallo Veríssimo; Mariana Bueno (Wiley, 2020)
Abstract The "Be sweet to babies" video is a knowledge translation tool targeted at parents on the use of analgesic strategies during painful procedures performed in neonates. This study aimed to evaluate the effectiveness of the Portuguese version of this video on maternal involvement in neonatal pain management during the newborn screening blood test. Nonrandomized, pragmatic clinical trial. The study was conducted in a rooming‐in unit. All mothers received a pamphlet regarding neonatal pain management and were invited to participate in daily education sessions conducted by nurses, which included the video. The intervention group included mothers who voluntarily watched the video, while the control group was comprised of mothers who did not attend the education sessions or left the session before watching the video. Data were collected by interviews conducted by the research team. Descriptive and inferential analysis considered a confidence interval of 95%. A total of 73 mothers were included in the study. Analgesic strategies were used in 14 (40%) of the procedures in the intervention group and 9 (24%) in the control group, a clinically important difference of 16% points between groups, although no statistically significant difference was found (P = .13). Breastfeeding was the most commonly used strategy. Watching the video increased the chance of implementing analgesic strategies by 2.1 times (P = .19), while nurses suggesting the use of analgesia increased this chance by 5.5 times (P = .006). Although no statistical significance was found, the results suggest the clinical significance and feasibility of the "Be sweet to babies" video as a KT tool targeted at parents on neonatal pain management during nonurgent painful procedures. In addition, maternal involvement in pain care significantly increased when pain relief strategies were recommended by nurses, which suggests that nurses have a key role in facilitating parental participation.